Humic Substance [Working Title] 2021
DOI: 10.5772/intechopen.96595
|View full text |Cite
|
Sign up to set email alerts
|

Role of Humic Substances in Formation of Safety and Quality of Poultry Meat

Abstract: The purpose of this chapter was to study the influence of humic substances on the formation of the safety and quality of poultry meat. The high abilities of the natural and organic complex of humic acids “Reasil®HumicHealth” (produced in Russia, Saratov) to sorb and desorb five mycotoxins of compound feed (aflatoxin B1, ochratoxin, toxin T-2, zearalenone and fuminisin B1) were experimentally established. The hepatoprotective ability of humic acids was observed in experiments on broilers using rapeseed meal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(2 reference statements)
0
1
1
Order By: Relevance
“…For example, a research study on the inclusion of humus substances in diets for Ross 308 broiler chickens conducted by El Kaya and Tuncer [67] established a higher weight gain and a lower feed conversion ratio in the research group of broiler chickens (1.68), which was 0.18 higher than that found in this study [67]. A research study conducted in Russia on Ross 308 broiler chickens whose diets were supplemented with humic acid 1 g, 1.5 g, and 2 g found that on day 38, the CY was in the range of 70.5%-73.0% [68]. Kocabagli et al [25] established that adding Farmagulator DRY Humate to broiler feed led to a higher carcass weight and yield (73.47%-74.18%) in the groups fed with the humic additive.…”
Section: Discussioncontrasting
confidence: 63%
“…For example, a research study on the inclusion of humus substances in diets for Ross 308 broiler chickens conducted by El Kaya and Tuncer [67] established a higher weight gain and a lower feed conversion ratio in the research group of broiler chickens (1.68), which was 0.18 higher than that found in this study [67]. A research study conducted in Russia on Ross 308 broiler chickens whose diets were supplemented with humic acid 1 g, 1.5 g, and 2 g found that on day 38, the CY was in the range of 70.5%-73.0% [68]. Kocabagli et al [25] established that adding Farmagulator DRY Humate to broiler feed led to a higher carcass weight and yield (73.47%-74.18%) in the groups fed with the humic additive.…”
Section: Discussioncontrasting
confidence: 63%
“…HSs are effective as dietary supplements, as they appear to have only a few side effects (and even those only in highly limited dietary conditions) [58]. HSs designated as the biologically active additives used in medical and veterinary medicine practice are positioned as enterosorbents, immunomodulators [59][60][61] and bioregulators of a new generation [62,63]. The immunomodulatory effect of HA was demonstrated by the course administration of HA isolated by the sodium pyrophosphate method from pine-sphagnum-cotton sedge peat reduced the general anaphylaxis reaction in mice and guinea pigs immunized with ovalbumin and decreased serum content of IgG1 and IgE in mice.…”
Section: The Influence Of Humic Substances On the Human Healthmentioning
confidence: 99%